2008
DOI: 10.1159/000124381
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal localization of nine porcine genes encoding transcription factors involved in adipogenesis

Abstract: Chromosomal localization of nine porcine genes encoding transcription factors involved in adipogenesis was determined. BAC clones harboring sequences of selected genes CEBPA (SSC6q12), CEBPB (SSC17q23), CEBPD (SSC4q15), CEBPG (SSC6q12), PPARG (SSC13q24), SREBF1 (SSC10q17), DDIT3 (SSC12q15), GATA2 (SSC13q24 →q31) and GATA3 (SSC5p12) were mapped by FISH. The positions of these genes in the human and pig genomes were compared. A potential role of the genes encoding adipogenesis factors as candidate genes for fatn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…We selected nine genes-seven of which are involved in adipogenesis (PPARG, SREBF1, CEBPA, CEBPB, CREB, FABP4, GATA2) and two that were used as control genes (SOX9, MYL1; Table 1). The genes were mapped by FISH to different porcine chromosomes, such as SSC4, SSC6, SSC12, SSC13, SSC15, and SSC17 (Szczerbal and Chmurzynska 2008;Szczerbal et al 2007a, b). We selected the genes so that adipogenic and control genes or pro-and anti-adipogenic genes were located on the same chromosome (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected nine genes-seven of which are involved in adipogenesis (PPARG, SREBF1, CEBPA, CEBPB, CREB, FABP4, GATA2) and two that were used as control genes (SOX9, MYL1; Table 1). The genes were mapped by FISH to different porcine chromosomes, such as SSC4, SSC6, SSC12, SSC13, SSC15, and SSC17 (Szczerbal and Chmurzynska 2008;Szczerbal et al 2007a, b). We selected the genes so that adipogenic and control genes or pro-and anti-adipogenic genes were located on the same chromosome (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…BAC probes for adipogenic genes were selected based on previous information about the gene localization (Szczerbal and Chmurzynska 2008;Szczerbal et al 2007a, b). BAC probes for control genes (MYL1, SOX9) were used for the first time in this study and were verified by PCR using specific primers (primer sequences available on request) and by fluorescence in situ hybridization (FISH) on metaphase chromosomes.…”
Section: Dna Probesmentioning
confidence: 99%
“…ACACA and SREBF1 , were localized in SSC12. The chromosomal location of SREBF1 was already shown earlier, mapping to SSC12q15 [Szczerbal and Chmurzynska, 2008], while ACACA was assigned to SSC12q12-q13. The location of ACACA is inconsistent with a previous mapping report [Calvo et al, 2000] in which the authors indicated the location in the p-arm of SSC12.…”
Section: Resultsmentioning
confidence: 52%
“…For example, porcine candidate genes, including nine genes encoding adipogenic transcription factors (174), are widely distributed among porcine chromosomes (174). Twenty-five candidate genes are localized on chromosomes 1, 2, 4-7, 9, 10, 12, 13, 17, and 18, with chromosome 6 containing 7 genes, whereas many other chromosomes contain one or two (174). It will be important to demonstrate which of the candidate genes are critical players by demonstrating functionality that results in a particular phenotype.…”
Section: Identification Of Genes Influencing Adipose Tissue Differentmentioning
confidence: 99%